1997
DOI: 10.1038/hdy.1997.184
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of gynodioecy in Plantago lanceolata L. I. Frequencies of male-steriles and their cytoplasmic male sterility types

Abstract: The maintenance of a gynodioecious breeding system (hermaphrodites and male-steriles) was studied in Plantago lanceolata. Cytoplasmic-nuclear inheritance is important in the maintenance of male-steriles. The male-sterile trait is cytoplasmically based (CMS), and male fertility can be restored by nuclear genes. Male-sterile frequencies differ among populations. Several hypotheses can be considered. (1) In each population a different equilibrium could be optimal because of environmentally dependent fitnesses. (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
2
16
1
Order By: Relevance
“…Several previous studies have documented the distribution of CMS‐types among natural plant populations, largely focused on gynodioecious species where the frequency of the CMS (female) phenotype varies geographically (e.g., Belhassen et al 1993; Cuguen et al 1994; de Haan et al 1997; Laporte et al 2001; Olson and McCauley 2002; Stadler and Delph 2002; Murayama et al 2004). Using cytoplasmic markers assumed to cosegregate with unique CMS genes, and in one case a CMS gene itself (Murayama et al 2004), these studies generally report large numbers of haplotypes and frequent polymorphism within and among populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have documented the distribution of CMS‐types among natural plant populations, largely focused on gynodioecious species where the frequency of the CMS (female) phenotype varies geographically (e.g., Belhassen et al 1993; Cuguen et al 1994; de Haan et al 1997; Laporte et al 2001; Olson and McCauley 2002; Stadler and Delph 2002; Murayama et al 2004). Using cytoplasmic markers assumed to cosegregate with unique CMS genes, and in one case a CMS gene itself (Murayama et al 2004), these studies generally report large numbers of haplotypes and frequent polymorphism within and among populations.…”
Section: Discussionmentioning
confidence: 99%
“…Predictions about the frequency, maintenance, and spatial distribution of particular CMS and Rf in populations of outcrossers are not always clear (reviewed in Olson et al 2005; Klaas and Olson 2006) To date, only a few studies have documented the distribution and frequency of CMS alleles in natural populations (e.g., Belhassen et al 1993; Cuguen et al 1994; de Haan et al 1997; Olson and McCauley 2002; Stadler and Delph 2002; Murayama et al 2004), all conducted in species in which the CMS phenotype is expressed in natural populations (gynodioecy). These studies have found that sterilizing cytotypes have a relatively wide geographic distribution, being present in multiple populations that are often polymorphic with respect to cytoplasmic haplotypes.…”
mentioning
confidence: 99%
“…CMS genes are assumed to follow rules of maternal inheritance whereas restorer of fertility (Rf) alleles are often assumed to be Mendelian and dominant to nonrestorer alleles (rf). In Plantago , Thymus , and Silene , however, even quite complex models for the genetics of inheritance that include two or more Rf loci, a mix between dominance and recessive gene action at different loci, and epistatic interactions among the loci often cannot account for sex ratio segregation within families (de Haan et al 1997; Charlesworth and Laporte 1998; Taylor et al 2001; Emery and McCauley 2002; van Damme et al 2004). These observations indicate that basic tenets of the inheritance of sex expression in gynodioecious species are still unknown.…”
Section: The Evolutionary Logic Of Gynodioecy: Current Thinkingmentioning
confidence: 99%
“…Both types can be found in the field, but MS1 occurs in relatively higher frequency (10% versus 2%), and in most populations (18 out of 20) compared to MS2. The studied plants originated from four populations, Ht (9% MSl), Leek (10% MSl, 3% MS2), Rei (10% MS2) and Kou (1% MSl) (de Haan et al, 1997b). The relative percentages of CMS types were estimated by molecular markers Ht (15% CMSI, 70% CMSII, 2% CMSIII), Leek (15% CMSI, 50% CMSII), Rei (65% CMSII, 35% CMSIII) and Kou (20% CMSII, 60% CMSIII) (de Haan et al, 1997b).…”
Section: Plantago Lanceolata Populationsmentioning
confidence: 99%
“…The studied plants originated from four populations, Ht (9% MSl), Leek (10% MSl, 3% MS2), Rei (10% MS2) and Kou (1% MSl) (de Haan et al, 1997b). The relative percentages of CMS types were estimated by molecular markers Ht (15% CMSI, 70% CMSII, 2% CMSIII), Leek (15% CMSI, 50% CMSII), Rei (65% CMSII, 35% CMSIII) and Kou (20% CMSII, 60% CMSIII) (de Haan et al, 1997b). In order to characterise the potential hermaphroditic parents for their CMS type presence or absence of restorer alleles for two CMS types were assessed.…”
Section: Plantago Lanceolata Populationsmentioning
confidence: 99%